Endogenous Price Commitment, Sticky and Leadership Pricing: Evidence from the Italian Petrol Market - Patrick Andreoli-Versbach; Jens-Uwe Franck (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2013)
This article studies dynamic pricing strategies in the Italian gasoline market before and after the market leader unilaterally announced its commitment to adopt a sticky-pricing policy. Using daily Italian firm level prices and weekly average EU prices, we show that the effect of the new policy was twofold. First, it facilitated price alignment and coordination on price changes. After the policy change, the observed pricing pattern shifted from cost-based to sticky-leadership pricing. Second, using a dif-in-dif estimation and a synthetic control group, we show that the causal effect of the new policy was to significantly increase prices through sticky-leadership pricing. Our paper highlights the importance of price-commitment by a large firm in order to sustain (tacit) collusion.
urn:nbn:de:bvb:19-epub-16182-5
Keywords: K21; K42; L13; L41; L71; 330; tacit collusion; leadership pricing; sticky pricing; endogenous commitment